Electropolymerised-hemin-catalysed reduction and analysis of tartrazine and sunset yellow. (1st October 2019) - Sun, Sin-Cih; Hsieh, Bo-Chuan; Chuang, Min-Chieh
Abstract: Colourants are widely added in various foods; nevertheless, recent research has revealed that the azo-colourants in foods pose a potential risk to human health. In the present study, the electropolymerised hemin electrode was demonstrated to efficiently catalyse the reduction of azo-colourants. Taking advantage of the ability of cyclic protoporphyrin to exhibit π−π stacking interactions with azo compounds and the capability of the central ferric ion to electrostatically attract the negatively charged sulfonate group, sulphonated azo compounds were readily adsorbed by hemin molecules, facilitating the redox reaction of azo compounds. In response to 2 μM tartrazine (TT), the hemin-functionalised electrode exhibited a well-defined wave in square wave voltammograms (SWVs), and the wave current was approximately 5-fold greater than the signal yielded with the bare electrode. The parameters of hemin electropolymerisation yielding the maximum sensitivity were investigated, leading to a limit of detection of 360 nM ( n  = 3). Furthermore, simultaneous analysis of TT and sunset yellow (SY) in a mixture was demonstrated to be feasible, with well-separated (Δ E  = 160 mV) voltammetric peaks obtained that corresponded to TT and SY. The electrode was also successfully tested with a drink-mimicking sample, indicating the negligible effects of oxygen and ions on analytical performance. To gain insight into the advanced catalytic property, catalytic kinetics were analysed, which revealed that the number of electrons transferred was 1.63 (for TT) and 1.67 (for SY). The reaction order of TT and SY was 2.7 and 1.8, respectively. The Tafel slope of TT and SY, derived from the polarisation curves, was 172 and 86 mV dec −1, respectively, and an approximately 33% increase in the exchange current was obtained compared with when the unmodified electrode was employed. The catalytic performance supports that electropolymerised hemin is a superior catalyst with promise for practical application in the detection of azo-colourants.